IT is never too late for changes? Analysing the relationship between process innovation, IT and older workers - Irene Bertschek; Jenny Meyer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
The paper analyses the relationship between two major challenges firms are faced to: using the potentials of information technologies (IT) as an enabler of process innovations on the one hand and an ageing workforce that might interfere these potentials on the other hand. Econometric results based on firm-level data from the German manufacturing and service sectors reveal that firms with a higher IT-intensity are more likely to introduce new or improved processes. Older workers are harmful to the probability of process innovation based on IT. Leaving the negative relationship between older workers and the probability to innovate unaffected, IT-specific training for older workers is conducive to the realisation of process innovations. Thus, not older workers in general are harmful to firms' innovation capabilities, but older workers who lack the appropriate IT skills.
Keywords: J14; L23; O31; 330; process innovation; information technology; older workers; Innovation; Computergestütztes Verfahren; Informationstechnik; Ältere Arbeitskräfte; Qualifikation; Deutschland